Stakeholders' evolutionary relationship analysis of China's national park ecotourism development. (15th August 2022) - Meng, Jidong; Long, Yong; Lefeng, Shi
Abstract: To mitigate the conflict of economic development and ecological protection, China government initiates its national park plan in recent years. In this stage, addressing the benefit contradictories among stakeholders is of importance. Around this issue, this paper focuses on the one of most keen-edged topics in China, which is how to deal well with the coordination issue among local government, tourism development enterprise and local residents. To disentangle the complexly dynamic relationships among them, a set of mathematical models are built and derived, based on evolutionary game theory. The corresponding results indicate that the intensity of regulation by local governments, the degree of compensation to ecotourism development projects by tourism development enterprises, and the participation degree of local residents to the projects are closely related to ultimate game stabilization; some propositions are gained accordingly, which suggest the bounded conditions to achieve the optimal stabilization. To validate and broaden the results, the relevant numerical simulation and discussion are provided. Highlights: The stakeholders relationship about China's National Park Ecotourism is discussed. The corresponding evolutionary game models are built and analyzed. The optimal conditions of advancing the ecotourism of national parks are put forth.